Ferritin in the Serum of Normal Subjects and Patients with Iron Deficiency and Iron Overload. Issue 5834 (28th October 1972) - Jacobs, A.; Miller, F.; Worwood, M.; Beamish, M. R.; Wardrop, C. A.
Abstract : The concentration of ferritin in serum gives a quantitative measure of the amount of storage iron in normal subjects and those with iron deficiency or overload. The mean level in normal men is 69 ng/ml, compared with 35 ng/ml in normal women. A concentration below 10 ng/ml is associated with a low transferrin saturation and iron-deficient erythropoiesis.